Facile Synthesis of MnO2/Polypyrrole/MnO2 Multiwalled Nanotubes as Advanced Electrocatalysts for the Oxygen Reduction Reaction. Issue 8 (7th May 2015) - Yuan, Haoran; Deng, Lifang; Tang, Jiahuan; Zhou, Shungui; Chen, Yong; Yuan, Yong
Abstract Efficient, low‐cost electrocatalysts for the oxygen reduction reaction are essential components of renewable energy technologies. Herein, hierarchical multiwalled MnO2/polypyrrole/MnO2 nanotubes (NT‐MPMs) were synthesized by using a simple, cost‐effective hydrothermal method. The key to fabricating the multiwalled NT‐MPMs was to introduce a conductive polypyrrole (PPy) interlayer to improve the electrical conductivity of the MnO2 nanotubes. In alkaline media, these rationally designed nanotubes exhibited remarkable electrocatalytic activity for the oxygen reduction reaction without the use of an external conductive additive, and significantly outperformed MnO2 nanotubes containing a carbon additive, MnO2/PPy nanotubes, and MnO2/PPy/MnO2 nanowires. A microbial fuel cell (MFC) equipped with the NT‐MPM cathode exhibited a maximum power density of 721±20 mW m−2, which is comparable to that of a Pt/C cathode. Furthermore, the NT‐MPM cathode had greater long‐term stability than the Pt/C cathode. The outstanding performance of the NT‐MPMs makes them a potential alternative to Pt/C in MFCs for sustainable energy generation.